Sequestration of toxic Pb (II) ions by base treated coconut (Cocos Nucifiera) palm frond powder / Mardhiah Ismail, Megat Ahmad Kamal Megat Hanafiah and Sarah Laila Mohd Jan - Ismail, Mardhiah; Megat Hanafiah, Megat Ahmad Kamal; Mohd Jan, Sarah Laila (2011)
The adsorption of Pb(JI) ions from aqueous solution using sodium hydroxide treated coconut palm (cocos nucifiera) frond powder was performed using batch experiment. The experiments were conducted to determine the factor effecting adsorption such as pH, initial heavy metal concentration and contact time. Adsorption was fast as equilibrium was achieved in less than 90 min, and was best described by pseudo-second order model. Based on the Langmuir model, the maximum adsorption capacities of Pb (ll) ion was found to be 45.45 mg g-1 . The highest amount of heavy metal adsorbed occurred at pH 4.